Komunitas Gastropoda pada Padang Lamun Perairan Pantai Manokwari - Adinda Rindiani Putri; Paskalina Th Lefaan; Rina Anita Mogea (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
This study was purposed to identify the spesies and the community structure of gastropods in Manokwari shore. The sampling used transect method at two observation stations, i.e Briosi BLK shore and Rendani shore. Each station has three transect lines parallel to the sea, each of which had 10 quadrats. These transects were placed on a seagrass beds. Data analysis was carried out including diversity index (H’), evenness index (E), dominance (D) and density of gastropods. The results showed that the water quality at both sampling locations could support the growth of gastropods. The species composition of the gastropods in two sampling locations consisted of 20 families, 28 genera, and 82 species. The diversity index (H’) in Briosi BLK shore was 3.14; evenness index (E) = 0,92; dominance (D) = 0,06 and density of gastropods 23,70 ind.m-2. The diversity index (H’) of gastropods in Rendani shore was 3,79 ; equitability index (E) = 0,90; dominance (D) = 0,03 and density of gastropods 83,33 ind.m-2 . Gastropods found were Strombus (Canarium) urceus urceus, Conus (Virroconus) coronatus, Chicoreus sp.2, Vexillum (Costellaria) mirabile, Polinices tumidus, and Imbricaria conularis. Based on the diversity index, the two stations are in a high diversity index so that there is no dominant species in the two locations, The gastropod density in Rendani shore was higher than that in Briosi BLK, it is suspected that the substrate is suitable and the amount of organic matter and then, far from the gathering place to support the growth of gastropods.